Improved Stable Isotope Dilution Assay for Dietary Folates Using LC-MS/MS and Its Application to Strawberries - Striegel, Lisa; Chebib, Soraya; Netzel, Michael E.; Rychlik, Michael (Frontiers in Chemistry, 2018)
Folates play an important role in the human body and a deficiency of this vitamin can cause several diseases. Therefore, a reliable analytical method is crucial for the determination of folate vitamers in strawberries and other dietary folate sources. A stable isotope dilution LC-MS/MS method for analyzing folates in food was developed and validated. The folate vitamers Pteroylmonoglutamic acid, tetrahydrofolate, 5-methyltetrahydrofolate and 5-formyltetrahydrofolate were quantified using 13C-labelled internal standards. Validation of the assay was accomplished by determining linearity, precision, recovery, limit of detection and limit of quantification and revealed to be a precise, sensitive and accurate method to determine folate vitamers. Strawberries are worldwide consumed and known to be a good dietary source of nutritive compounds. Using this method, folate concentrations in selected commercial strawberry cultivars and experimental breeding lines grown in Germany were investigated. Total folates varied from 59 to 153 µg/100 g on fresh weight basis. Furthermore, folate content after lyophilizing or freezing did not show any significant differences compared to fresh strawberries. However, significant losses of total folates in pureed strawberries could be observed after 5 days of storage with only 16 % of the original concentration retained. In summary, some of the investigated strawberry cultivars/breeding lines can be considered as rich dietary sources of natural folates.